Diversity of insulin and IGF signaling in breast cancer: Implications for therapy - Lero, Michael W.; Shaw, Leslie M. (Molecular and cellular endocrinology, 2021)
This review highlights the significance of the insulin receptor (IR) and insulin-like growth factor-1 receptor (IGF-1R) signaling pathway in cancer and assesses its potential as a therapeutic target. Our emphasis is on breast cancer, but this pathway is central to the behavior of many cancers. An understanding of how IR/IGF-1R signaling contributes to the function of the normal mammary gland provides a foundation for understanding its aberrations in breast cancer. Specifically, dysregulation of the expression and function of ligands (insulin, IGF-1 and IGF-2), receptors and their downstream signaling effectors drive breast cancer initiation and progression, often in a subtype-dependent manner. Efforts to target this pathway for the treatment of cancer have been hindered by several factors including a lack of biomarkers to select patients that could respond to targeted therapy and adverse effects on normal metabolism. To this end, we discuss ongoing efforts aimed at overcoming such obstacles.